ChemInform Abstract: Review of Pt‐Based Bimetallic Catalysis: From Model Surfaces to Supported Catalysts. Issue 6 (20th February 2013) - Yu, Weiting; Porosoff, Marc D.; Chen, Jingguang G.
Abstract Review: 423 refs.